Fabrication And Characterization Of Polylactic Acid (PLA) Blend Biomaterial Using 3D Printing For Potential Application In Tissue Engineering - Chow, Li Chin (Universiti Sains Malaysia, 2018)
In this study, it was to study the effect of plasticizer on the mechanical properties of three-dimensional (3D) printed polylactic acid (PLA) blend system, for potential application as scaffolding material in tissue engineering. The PLA was plasticized with Polyethylene glycol (Mw-6,000 g/mol) or Triethylene glycol (Mw-150 g/mol) in various plasticizer concentrations (0, 5, 10, 15, 20, and 25 wt%) using single screw extrusion. With the incorporation of such plasticizer into PLA matrix, the toughness properties e.g. elongation at break and impact strength of PLA specimen improved due to reduce in stiffness of plasticized PLA. Nevertheless, the tensile and flexural strength decreases, as compared to neat PLA. In related to plasticizer content, the plasticized PLA achieved optimum mechanical performance at 10 wt% and 15 wt% respectively for PEG and TEG. Fourier transform infrared (FTIR) spectroscopy reveals the physical interaction between PLA and its plasticizer. Differential scanning calorimetry (DSC) study reveals decrease in glass transition temperature as concentration of plasticizer increases. However, some extent of phase separation has been found when PEG and TEG incorporated greater than 10 wt% and 15 wt% respectively. Scanning electron microscopy (SEM) observations reveals the plasticizer lump in the PLA matrix at high concentration of plasticizer. Besides, the mechanical properties obtained from 3D printed specimen were lower than compression molding technique. However, the developed 3D printed plasticized PLA had achieved desired mechanical flexibility improvement with acquired strength for support tissue regeneration in scaffold.